Unfolding Trade Effect in Two Margins of Informality. The Peruvian Case - Camila Cisneros-Acevedo (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper studies the effect of an increase in import competition on informality along two margins. I consider the extensive margin, where workers are hired by unregistered employers and the intensive margin, where even though jobs are carried out in registered firms, employees are off the books. Peru's relentless informal employment and its unprecedented trade-driven growth provides an ideal case study. Using a rich household survey, I find that exposure to trade impacts on informality through two competing and contrasting mechanisms. On the one hand, extensive-informal employment declines as unregistered employers shrink or exit due to their low productivity. On the other hand, intensive-informal employment rises as registered employers reduce costs by hiring informal workers. Furthermore, results suggest that the intensive margin drives the overall effect. Hence, I find that trade liberalisation increases informality.
Keywords: F16; F14; J46; 330; trade liberalization; labour informality; Peru